Participatory mapping of transboundary pollution: the case of Imperial Beach, California - Maione, Carol; Fernandez, Gabriela; Vito, Domenico (Frontiers in Sustainable Tourism, 2024)
Transboundary pollution is a major global challenge as its sources, causes, and movement remains unknown and unsurveyed. Monitoring beach litter along international borders can reveal some of the pathways by which litter enters water bodies, and hence advance the implementation of measures to prevent pollution emissions into international waters. In this paper, participatory mapping was used to detect beach litter in Imperial Beach, California, along the U.S.-Mexico international border. This study implemented a 3-step protocol including an introductory awareness workshop, a macro-debris survey to categorize and remove beach litter, and a qualitative assessment of pollution drivers. Results show that plastic litter is the most dominant across all transects (304 debris, 52.6% of all litter observations), with an average density of 76 pieces/transect, with plastic tableware, wrappings, and polystyrene being the most common materials. Participants identified some of the major causes of pollution with paucity of waste management facilities, tourism activities near/on the beach, and inflow of pollution across the border.